Vasily Kirey: «Ukrainian General» in Wrangel's Crimea - A. A. Chemakin (Омский научный вестник: Серия "Общество. История. Современность")
The article is devoted to a little-studied aspect of the biography of the Russian artilleryman Major General Vasily Fadeevich Kirey (1879–1942), related to his political work in Wrangel’s Crimea in 1920. The research is based on unpublished sources from the collections of seven archives, as well as press materials and memoirs. Interpreting them using an anthropological approach, problem-chronological and biographical methods, the author reconstructs the biography of General Kirey with an emphasis on his activities as a general for assignments on Ukrainian affairs (“Ukrainian general”) under the Commander-in-Chief of the Armed Forces of South Russia, as well as his role as an emissary in negotiations with Petliurists.